Crossing Sidelines, Crossing Cultures: Sport and Asian Pacific American Cultural Citizenship - Franks, Joel (Hamilton Books, 2009)
Since Crossing Sidelines, Crossing Cultures was originally published in 2000, new findings in Asian Pacific American sports have come to light. Moreover, Americans of Asian Pacific ancestry have made the sports world incredibly more exciting than before. Crossing Sidelines, Crossing Cultures tells intriguing tales of athletes, now often forgotten-such as aquatic legend Duke Kahanamoku, diving gold medalist Vicki Manalo, courageous female golfer Jackie Liwai Pung, and baseball pioneer Buck Lai. It explores how Asian Pacific Americans have asserted a vibrant, joyful sense of community through sports, while encountering racism and nativism. Since 2000, talented athletes of Asian Pacific ancestry have emerged-athletes such as the great Tiger Woods, but also Tim Lincicum, Troy Polamalu, Bryan Clay, Natasha Kai, and Logan Tom. These athletes have chipped away at prevailing stereotypes, and their stories, too, will be told in this second edition of Crossing Sidelines, Crossing Cultures.